Does tibial design modification improve implant stability for total knee arthroplasty?: An experimental cadaver study - Jäger, Sebastian; Eissler, Marvin; Schwarze, Martin; Schonhoff, Mareike; Kretzer, Jan Philippe; Bitsch, Rudi G. (Bone & joint research, 2022)
Aims - - One of the main causes of tibial revision surgery for total knee arthroplasty is aseptic loosening. Therefore, stable fixation between the tibial component and the cement, and between the tibial component and the bone, is essential. A factor that could influence the implant stability is the implant design, with its different variations. In an existing implant system, the tibial component was modified by adding cement pockets. The aim of this experimental in vitro study was to investigate whether additional cement pockets on the underside of the tibial component could improve implant stability. The relative motion between implant and bone, the maximum pull-out force, the tibial cement mantle, and a possible path from the bone marrow to the metal-cement interface were determined. - - Methods - - A tibial component with (group S: Attune S+) and without (group A: Attune) additional cement pockets was implanted in 15 fresh-frozen human leg pairs. The relative motion was determined under dynamic loading (extension-flexion 20° to 50°, load-level 1,200 to 2,100 N) with subsequent determination of the maximum pull-out force. In addition, the cement mantle was analyzed radiologically for possible defects, the tibia base cement adhesion, and preoperative bone mineral density (BMD). - - Results - - The BMD showed no statistically significant difference between both groups. Group A showed for all load levels significantly higher maximum relative motion compared to group S for 20° and 50° flexion. Group S improved the maximum failure load significantly compared to group A without additional cement pockets. Group S showed a significantly increased cement adhesion compared to group A. The cement penetration and cement mantle defect analysis showed no significant differences between both groups. - - Conclusion - - From a biomechanical point of view, the additional cement pockets of the component have improved the fixation performance of the implant. - - Cite this article: Bone Joint Res 2022;11(4):229-238.
Gesehen am 17.08.2022